Weak interactions effect on the p–n mass splitting and the principle of equivalence - Chamoun, Nidal (2002)
The weak interaction contribution to the proton–neutron mass difference is computed using a generalization of Cottingham's formula. When included in the analysis of the Eotvos experiment, this contribution reduces the bound on a possible weak interactions violation to the equivalence principle by one order of magnitude.